Keseimbangan Tanggung Jawab Hukum antara Multinational Corporation dan Negara Tuan Rumah dalam Foreign Direct Investment di Indonesia - Prissly Lionny Ilela (Media Hukum Indonesia (MHI), 2026)
This study discusses the balance of responsibility between multinational corporations (MNCs) and host countries in the management of Foreign Direct Investment (FDI) in Indonesia. The main legal issue lies in how MNCs' obligations and responsibilities relate to national law and how host countries create legal certainty and oversee the implementation of foreign investment in line with national interests. The purpose of this study is to analyze the legal position of MNCs in the implementation of FDI, the role of host countries in creating a balance of responsibilities, and the dynamics of the relationship between MNCs and Indonesia, which is often marked by conflicts of economic interests and national sovereignty. This study uses a normative-empirical legal research method, with a legislative, case, and conceptual approach. The results show that MNCs are obliged to comply with national laws, implement corporate social responsibility (CSR), and preserve the environment. The host country plays an important role in providing legal certainty, protection, and investment facilities through policies such as the Job Creation Law and the Online Single Submission (OSS) system. However, overlapping central and regional authorities and weak implementation of implementing regulations remain obstacles. The case of PT Freeport Indonesia illustrates that through negotiation and dialogue, conflicts between MNCs and the government can be resolved with a win-win solution that benefits both parties.